2018
DOI: 10.1139/apnm-2018-0057
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal damage following short-duration exercise at the same relative intensity is similar in temperate and hot environments

Abstract: Increasing temperature and exercise disrupt tight junctions of the gastrointestinal tract although the contribution of environmental temperature to intestinal damage when exercising is unknown. This study investigated the effect of 2 different environmental temperatures on intestinal damage when exercising at the same relative intensity. Twelve men (mean ± SD; body mass, 81.98 ± 7.95 kg; height, 182.6 ± 7.4 cm) completed randomised cycling trials (45 min, 70% maximal oxygen uptake) in 30 °C/40% relative humidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 50 publications
3
11
0
Order By: Relevance
“…We found significant increase in serum LPS and I-FABP only in PEx group of rats, which directly coincided with a lower presence of TJ proteins in this group. Our observations are in line with results of other authors, who observed elevated levels of LPS, similar to florid sepsis occures in ultramarathon runners (Bosenberg et al 1988;Walsh et al 2011) and increase in serum I-FABP level after high-intensity exercise (Pugh et al 2017;Sheahen et al 2018). However, BSB3 treatment prevented damage of intestinal barrier and release of LPS and I-FABP into circulation after exercise.…”
Section: Discussionsupporting
confidence: 93%
“…We found significant increase in serum LPS and I-FABP only in PEx group of rats, which directly coincided with a lower presence of TJ proteins in this group. Our observations are in line with results of other authors, who observed elevated levels of LPS, similar to florid sepsis occures in ultramarathon runners (Bosenberg et al 1988;Walsh et al 2011) and increase in serum I-FABP level after high-intensity exercise (Pugh et al 2017;Sheahen et al 2018). However, BSB3 treatment prevented damage of intestinal barrier and release of LPS and I-FABP into circulation after exercise.…”
Section: Discussionsupporting
confidence: 93%
“…All included studies had been published in peer reviewed scientific journals at the time of inclusion. Within the included studies, 20 studies measured plasma i-FABP [4,9,11,12,20,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47], while 15 studies measured the urinary L/R or L/M ratio (DS/MS) [7,9,11,12,18,28,36,41,[48][49][50][51][52][53]. Studies assessing gut permeability via the urinary excretion ratio of lactulose to rhamnose/mannitol (L/R or L/M) provided a range of dosages from 1g (n = 2), 5g (n = 12) to 10g (n = 1) of lactulose in combination with 0.5-5g of rhamnose (or 2-5g of mannitol).…”
Section: Resultsmentioning
confidence: 99%
“…A hot environment may exacerbate both gut damage and permeability via increases in thermal stress in conjunction with gut hypoxia [19]. However, results are conflicting as to whether any of these factors (heat, intensity, duration) take a dominant lead in increasing the risk of gut damage [6,20,21]. Unfortunately, there are few studies that have had the capacity to examine the relative importance and contribution of each of these factors, and their interaction in either laboratory or race (more ecologically valid) settings.…”
Section: Introductionmentioning
confidence: 99%
“…These conclusions were recently substantiated following one hour of low intensity (50-70% watt max ) cycling, where I-FABP concentration increased following performance in a hot (35 • C/53% RH; 140%), but not temperate (20 • C/55% RH; 29%) ambient environment [142]. Importantly, these observations have been directly attributed to the influence of ambient temperature on whole-body thermal strain, given that when relative exercise-intensity is matched (VO 2max , T core , heart rate), the influence of ambient heat stress (20 vs. 30C • ) on I-FABP responses is abolished [145]. One study reported GI TJ breakdown (claudin-3) to increase to a similar extent following one hour of running in a temperate (22 • C/62% RH) versus hot (33 • C/50% RH) ambient environment [147], suggestive that TJ breakdown is insensitive to thermal stress.…”
Section: Severity Of Gi Barrier Integrity Loss Following Exertional-hmentioning
confidence: 99%
“…In comparison, since initial investigation [86], no studies have monitored the magnitude and time-course of I-BABP responses following exercise. Several studies have attempted to elucidate the influence of ambient temperature on GI epithelial injury [115,124,142,145,146]. Compared with modest increases in I-FABP (127%) following two hours of moderate intensity cycling (60% VO 2max ) in temperate (22 • C/44% RH) conditions (peak T core 38.1 • C), performance of matched exercise in both mild (30 • C/35% RH [115]) and severe heat stress conditions (35 • C/26% RH; [124]) vastly enhanced peak T core (38.4 • C and 39.6 • C) and percentage change in I-FABP (184% and 432%) responses, respectively.…”
Section: Severity Of Gi Barrier Integrity Loss Following Exertional-hmentioning
confidence: 99%